Peran jejak literasi (JeLi) Perpustakaan Umum Bahagia Mendawai dalam meningkatkan minat baca - Bahrony, Dian Apriliani; Latifa Hanum, Atiqa Nur; Madeten, Sisilya Saman (Pustaka Karya : Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2023)
In improving reading interest and creativity strategies in children, it is necessary to attract their attention. Nowadays, children prefer to learn while playing so that they are not only focused on the material but also on the fun. This study aims to determine the role of Jejak Literasi (JeLi) Bahagia Mendawai Public Library in fostering children's creativity and its supporting factors. Researchers used descriptive qualitative methods and data collection was carried out using non-participant observation techniques, interviews with 10 informants and documentary studies to strengthen the findings. Data analysis was carried out by reducing data, presenting data and drawing conclusions. The results of this study show that Jejak Literasi (JeLi) activities as a forum for children to increase their interest in reading and have an impact on changes for them to learn while playing, especially children outside Kampung Caping Pontianak for free. Supporting factors for Jejak Literasi (JeLi) play an important role such as reading carts, collaboration communities, library board members and mobile library cars and other facilities. The learning gained from JeLi also helps them at school such as counting, reading, listening, coloring and writing.